Late Onset of ANCA Vasculitis as a Side Effect of Levamisole Treatment in Nephrotic Syndrome - Silvia Bernardi; Samantha Innocenti; Marina Charbit; Olivia Boyer (Medicina, 2022)
Levamisole is effectively used in steroid-dependent nephrotic syndrome and the more frequent side effects reported are cytopenia and liver enzymes alterations. Several studies have demonstrated that this drug can induce high titers of circulating perinuclear antineutrophil cytoplasmic autoantibodies (ANCA) and vasculitis, most of them occurring in the case of prolonged use. A four-year-old boy that was affected with steroid-dependent nephrotic syndrome was treated with Levamisole as a steroid-sparing agent at a dose of 2 mg/kg/48 h. After initiation of the treatment, the number of relapses drastically decreased, enabling a significant reduction in the cumulative steroid dose. Levamisole was well tolerated, and was therefore administered for several years. At the age of 15, he was also diagnosed with celiac disease. After nine years of continuous Levamisole treatment, he presented with a high fever, hand and foot joint arthritis, and increased levels of total and direct bilirubin. Since the symptoms started two days after the injection of the second dose of the COVID-19 vaccine, it was initially concluded that these manifestations were rare vaccination side effects. Therefore, he did not receive any specific treatments, and Levamisole was continued at the same dose. After an initial improvement, two months later, the patient presented with the same symptoms. Suspecting Levamisole-induced vasculitis, an ANCA titer was measured and this returned positive. Clinical manifestations and double positivity for both myeloperoxidase (MPO) and anti-proteinase 3 (PR3) antibodies argued against the fact that that these findings were secondary to vaccination, cocaine abuse, or celiac disease. Assuming that we were facing a rare drug reaction, Levamisole was promptly interrupted. This resulted in a rapid remission of fever and arthritis improvement, and a decrease in ANCA titers. By reporting this case, we want to raise awareness among clinicians regarding a rare complication of treatment with Levamisole that is often misdiagnosed due to the fact that the current literature lacks univocal guidelines regarding the precise timing of ANCA titrations and the duration of the treatment.